EXPERIMENTAL DETERMINATION OF THE STABILITY AND STOICHIOMETRY OF SULPHIDE COMPLEXES OF SILVER(I) IN HYDROTHERMAL SOLUTIONS TO 400°C - Stefansson A.; Seward T.M. (My University, 2003)
The solubility of silver sulphide (acanthite/argentite) has been measured in aqueous sulphide solutions between 25 and 400°C at saturated water vapour pressure and 500 bar to determine the stability and stoichiometry of sulphide complexes of silver(I) in hydrothermal solutions. The experiments were carried out in a flow-through autoclave, connected to a high-performance liquid chromatographic pump, titanium sampling loop, and a back-pressure regulator on line. Samples for silver determination were collected via the titanium sampling loop at experimental temperatures and pressures. The solubilities, measured as total dissolved silver, were in the range 1.0 × 10−7 to 1.30 × 10−4 mol kg−1 (0.01 to 14.0 ppm), in solutions of total reduced sulphur between 0.007 and 0.176 mol kg−1 and pHT,p of 3.7 to 12.7. A nonlinear least squares treatment of the data demonstrates that the solubility of silver sulphide in aqueous sulphide solutions of acidic to alkaline pH is accurately described by the reactions0.5Ag2S(s) + 0.5H2S(aq) = AgHS(aq) Ks,1110.5Ag2S(s) + 0.5H2S(aq) + HS− = Ag(HS)2− Ks,122Ag2S(s) + 2HS− = Ag2S(HS)22− Ks,232where AgHS(aq) is the dominant species in acidic solutions, Ag(HS)2− under neutral pH conditions and Ag2S(HS)22− in alkaline solutions. With increasing temperature the stability field of Ag(HS)2− increases and shifts to more alkaline pH in accordance with the change in the first ionisation constant of H2S(aq). Consequently, Ag2S(HS)22− is not an important species above 200°C. The solubility constant for the first reaction is independent of temperature to 300°C, with values in the range logKs,111 = −5.79 (±0.07) to −5.59 (±0.09), and decreases to −5.92 (±0.16) at 400°C. The solubility constant for the second reaction increases almost linearly with inverse temperature from logKs,122 = −3.97 (±0.04) at 25°C to −1.89 (±0.03) at 400°C. The solubility constant for the third reaction increases with temperature from logKs,232 = −4.78 (±0.04) at 25°C to −4.57 (±0.18) at 200°C. All solubility constants were found to be independent of pressure within experimental uncertainties. The interaction between Ag+ and HS− at 25°C and 1 bar to form AgHS(aq) has appreciable covalent character, as reflected in the exothermic enthalpy and small entropy of formation. With increasing temperature, the stepwise formation reactions become progressively more endothermic and are accompanied by large positive entropies, indicating greater electrostatic interaction. The aqueous speciation of silver is very sensitive to fluid composition and temperature. Below 100°C silver(I) sulphide complexes predominate in reduced sulphide solutions, whereas Ag+ and AgClOH− are the dominant species in oxidised waters. In high-temperature hydrothermal solutions of seawater salinity, chloride complexes of silver(I) are most important, whereas in dilute hydrothermal fluids of meteoric origin typically found in active geothermal systems, sulphide complexes predominate. Adiabatic boiling of dilute and saline geothermal waters leads to precipitation of silver sulphide and removal of silver from solution. Conductive cooling has insignificant effects on silver mobility in dilute fluids, whereas it leads to quantitative loss of silver for geothermal fluids of seawater salinity.